Impact of tumour thickness on survival after radical radiation and surgery in malignant pleural mesothelioma. Issue 3 (16th March 2017) - de Perrot, Marc; Dong, Zhi; Bradbury, Penelope; Patsios, Demetris; Keshavjee, Shaf; Leighl, Natasha B.; Hope, Andrew; Feld, Ronald; Cho, John
Tumour thickness was assessed to determine if this parameter could refine patients' selection for multimodality therapy in malignant pleural mesothelioma. We reviewed 65 consecutive treatment-naïve malignant pleural mesothelioma patients undergoing surgery for mesothelioma after radiation therapy (SMART). Total tumour thickness was determined by measuring the maximal thickness on nine predefined sectors on the chest wall, mediastinum and diaphragm. After a median follow-up of 19 months, 40 patients (62%) developed recurrence and 36 died (55%). Total tumour thickness, ranging between 2.4 and 21 cm (median 6.9 cm), correlated with tumour volume (p<0.0001, R 2 =0.29) and maximum standardised uptake value (p=0.006, R 2 =0.11). Total tumour thickness had a significant impact on overall survival and disease-free survival in univariate analysis. In multivariate analysis, total tumour thickness remained an independent predictor of survival (p=0.02, hazard ratio (HR) 1.12, 95% CI 1.02–1.23) and disease-free survival (p=0.01, HR 1.13, 95% CI 1.03–1.24) along with epithelial histologic subtype (p<0.0001, HR 0.25, 95% CI 0.13–0.50) and pN2 disease (p=0.03, HR 2.15, 95% CI 1.07–4.33). Diaphragmatic tumour thickness correlated best with time to recurrence (p=0.002, R 2 =0.22) and time to death (p=0.003, R 2 =0.2). The impact of tumour thickness on survival and disease-free survival independent of histologic subtypes and nodal disease is extremely encouraging. This parameter could potentially be used to refine the clinical staging of malignant pleural mesothelioma and optimise patient selection for radical treatment. Tumour thickness is an independent predictor of outcome after radical treatment for malignant pleural mesothelioma http://ow.ly/KCbT306wDBN